Effect of partner–agent model practice on microinsurance client value: Insight from microfinance institutions in Tanzania - Isidore Minani; Esther K. Ishengoma; Neema Mori (Cogent Business & Management, 2018)
In absence of formal microinsurance to protect low-income people against natural and man-made disasters, the partnership between insurance companies and microfinance institutions (MFIs), also known as the Partner–Agent Model (PAM), is gaining global recognition from governments, practitioners, and donors for its potential role to deliver microinsurance. Although the model is still nascent in Tanzania, it has significantly increased microinsurance outreach. However, while the microinsurance landscape has been extensively studied, the effect of PAM practice on mandatory microinsurance client value has not received much attention. Therefore, this study examines how the PAM practice affects microinsurance client value dimensions. Surveys were used to collect quantitative data from 229 managers of MFIs involved in PAM, randomly selected from 10 regions in Tanzania. The study applies structural equation modeling, particularly the regression analysis, to examine the effect of PAM practice on the appropriateness, accessibility, affordability, and responsiveness of PAM microinsurance services. Study findings indicate that though the PAM practice has a statistically significant positive effect on microinsurance client value, the client value does not score well on its four dimensions. Improvement and regulation of PAM practice is recommended to foster microinsurance client value.
Keywords: 650